Exposure to disinfection by-products in swimming pools and biomarkers of genotoxicity and respiratory damage – The PISCINA2 Study. (October 2019) - Font-Ribera, Laia; Marco, Esther; Grimalt, Joan O.; Pastor, Susana; Marcos, Ricard; Abramsson-Zetterberg, Lilianne; Pedersen, Marie; Grummt, Tamara; Junek, Ralf; Barreiro, Esther; Heederik, Dick; Spithoven, Jack; et al.
Abstract: Background: Swimming in pools is a healthy activity that entails exposure to disinfection by-products (DBPs), some of which are irritant and genotoxic. Objectives: We evaluated exposure to DBPs during swimming in a chlorinated pool and the association with short-term changes in genotoxicity and lung epithelium permeability biomarkers. Methods: Non-smoker adults (N = 116) swimming 40 min in an indoor pool were included. We measured a range of biomarkers before and at different times after swimming: trihalomethanes (THMs) in exhaled breath (5 min), trichloroacetic acid (TCAA) in urine (30 min), micronuclei in lymphocytes (1 h), serum club cell protein (CC16) (1 h), urine mutagenicity (2 h) and micronuclei in reticulocytes (4 days in a subset, N = 19). Several DBPs in water and trichloramine in air were measured, and physical activity was extensively assessed. We estimated interactions with polymorphisms in genes related to DBP metabolism. Results: Median level of chloroform, brominated and total THMs in water was 37.3, 9.5 and 48.5, μg/L, respectively, and trichloramine in air was 472.6 μg/m 3 . Median exhaled chloroform, brominated and total THMs increased after swimming by 10.9, 2.6 and 13.4, μg/m 3, respectively. Creatinine-adjusted urinary TCAA increased by 3.1 μmol/mol. Micronuclei in lymphocytes and reticulocytes, urine mutagenicity and serum CC16 levels remained unchanged after swimming. Spearman correlation coefficients showed no association between DBP exposure and micronuclei in lymphocytes, urine mutagenicity and CC16. Moderate associations were observed for micronuclei in reticulocytes and DBP exposure. Conclusions: The unchanged levels of the short-term effect biomarkers after swimming and null associations with personal estimates of exposure to DBPs suggest no measurable effect on genotoxicity in lymphocytes, urine mutagenicity and lung epithelium permeability at the observed exposure levels. The moderate associations with micronuclei in reticulocytes require cautious interpretation given the reduced sample size. Highlights: We evaluated swimmers' exposure to disinfection by-products in exhaled air and urine. We measured short-term effects on genotoxicity and lung damage biomarkers. Chloroform and brominated THMs levels in exhaled breath increased after swimming. Most of the effect biomarkers did not change after swimming. Associations were found for micronuclei in reticulocytes but sample size was small.